Patterning mechanisms in the body trunk and the appendages of Drosophila. - Morata, G.; Sanchez-Herrero, E. (Development, 1999)
During evolution, many animal groups have developed specialised outgrowths of the body wall, limbs or appendages. The type of appendage depends on the identity of the segment where they appear, indicating that the Hox genes contribute to appendage specification. Moreover, work carried out principally in Drosophila has identified the gene products and the mechanisms involved in pattern formation in the appendages. In this essay, we compare the morphogenetic processes in the appendages and the body wall; the function of the Hox genes and the response to the signalling molecules involved in local patterning. We speculate that, although the basic mechanisms are similar, there are significant differences in the manner the body trunk and appendages respond to them.